The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00284-010-9676-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Region on Fecal Microflora in Elderly Subjects Living in Bama, Guangxi, China

Abstract: Intestinal microflora analysis was performed on 52 healthy elderly subjects of different ages and in different regions in Bama County, Guangxi, China. The participants were assigned to three groups depending on their age and location: longevous (group M; mean age = 98 years; n = 21); rural younger elderly (group S; mean age = 70 years; n = 18); and urban elderly (group C; mean age = 82 years; n = 13). Ten groups of bacteria were quantified using real-time PCR. Age-related differences were observed in the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
4
23
1
Order By: Relevance
“…Although the abundance of these strains (two Bacteroides strains and one Ruminococcaceae strain) decreased with host age, they "preferred living" in the rural elderly in Bama. Similar results were also obtained in our previous study: a high level of Bacteroides-Prevotella was observed in the rural longevous participants of Bama (Zhao et al, 2010). These results suggested that living in the rural region of Bama could "enrich" these potential beneficial strains, and "keep" them from decreasing with the age of the elderly.…”
Section: Summary Of Band Identification and Significant Bacterial Asssupporting
confidence: 92%
See 3 more Smart Citations
“…Although the abundance of these strains (two Bacteroides strains and one Ruminococcaceae strain) decreased with host age, they "preferred living" in the rural elderly in Bama. Similar results were also obtained in our previous study: a high level of Bacteroides-Prevotella was observed in the rural longevous participants of Bama (Zhao et al, 2010). These results suggested that living in the rural region of Bama could "enrich" these potential beneficial strains, and "keep" them from decreasing with the age of the elderly.…”
Section: Summary Of Band Identification and Significant Bacterial Asssupporting
confidence: 92%
“…3), who was a longevous female living in the rural region of Bama. This is consistent with our previous study, in which as high as 9.5% of Bifidobacterium in total intestinal bacteria was observed in the same subject (Zhao et al, 2010). Although not each longevous participant in Bama has such high abundance of Bifidobacterium in their intestine, an unusually high level of these bacteria in several longevous people suggest an interesting relationship between Bifidobacterium and human aging.…”
Section: Summary Of Band Identification and Significant Bacterial Asssupporting
confidence: 91%
See 2 more Smart Citations
“…longum BBMN68 was isolated from a healthy centenarian in the Bama County of the Guangxi Zhuang Autonomous Region in China, which is famous for having a population with a high life-expectancy. Previous study showed that the proportion of bifidobacteria could reach up to 9.59% in the feces from the 90 -109 years old population in a Bama suburb using real-time PCR and denaturing gradient gel electrophoresis (20,21). Further study in our research group indicated that several remarkable characteristics of strain BBMN68 at the genome level, such as a higher abundance of genes associated with carbohydrate transport-metabolism category and two genes encoding bacteriocin, may be beneficial to the long-term colonization of BBMN68 in the human GIT (22).…”
mentioning
confidence: 99%